Low-dose Methotrexate has Similar Outcomes to High-dose Methotrexate in Combination with Anti-TNF Therapy in Inflammatory Bowel Diseases. (19th March 2019) - Borren, Nienke Z; Luther, Jay; Colizzo, Francis P; Garber, John G; Khalili, Hamed; Ananthakrishnan, Ashwin N
Abstract: Background and Aims: Methotrexate [MTX] is a well-known immunomodulator in the treatment of inflammatory bowel disease [IBD] and is often combined with biologic agents. The ideal MTX dose for combination therapy has not been determined. This study aimed to investigate the effect of varying doses of MTX on efficacy and safety outcomes when used with anti-TNF agents in IBD. Methods: This study included patients with Crohn's disease [CD] or ulcerative colitis [UC] receiving care between January 2005 and June 2018. Low-dose MTX was defined as ≤12.5 mg/week and high-dose as >12.5 mg/week. The primary efficacy outcome was a composite of need for IBD-related hospitalization or surgery, steroid initiation, or change of biologic agent within 1 year. Safety outcomes included side effects related to MTX, serious infections, malignancy, and need to discontinue MTX therapy within 1 year. Multivariable logistic regression models adjusting for relevant covariates were used to assess independent association between MTX dose and outcomes. Results: Our study included 222 patients with IBD [163 CD, 59 UC]. Just under a third were receiving low-dose MTX [28%]. The primary efficacy composite outcome was noted in 75 patients [47%] in the high-dose MTX group compared with 23 patients [37%] in the low-dose MTX group [ p = 0.15]. We found no significant associations between MTX dose and any side effect [odds ratio 1.59, 95% confidence interval 0.77–3.31, p = 0.21] or development of serious infections [odds ratio 1.19, 95% confidence interval 0.41–3.45, p = 0.76]. Conclusions: Low-dose and high-dose MTX combination therapy were equally effective, and no difference in infection or malignancy rates was observed.